2017
DOI: 10.15567/mljekarstvo.2017.0404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non nutritional factors on milk urea concentration and its relationship with production and fertility traits in Vojvodina dairy herds

Abstract: The purpose of this study was to examine possible relationship between milk urea and fertility of dairy cows using field data. This study also evaluated the influence of environmental factors on milk urea (MU) and the relationship between MU and daily milk yield, milk fat and protein percentage. The data were collected at 11 dairy farms in the Vojvodina region. Reproductive data and MU measurements were obtained from cows that calved between June 2013 and October 2015 and had a successful conception after calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The average MU in each of the first 3 lactations ranged from 24.80 to 26.19 mg/dL, which were similar to those reported by Bastin et al (2009) for the first-parity average MU (25.51 mg/dL) of dairy cows in Walloon. These values were also consistent with those reported in previous studies (Čobanović et al, 2017;Lopez-Villalobos et al, 2018;Ariyarathne et al, 2019). However, Satoła et al (2017b) reported a lower value for MU in Polish Holstein-Friesian cows.…”
Section: Descriptive Statisticssupporting
confidence: 93%
See 1 more Smart Citation
“…The average MU in each of the first 3 lactations ranged from 24.80 to 26.19 mg/dL, which were similar to those reported by Bastin et al (2009) for the first-parity average MU (25.51 mg/dL) of dairy cows in Walloon. These values were also consistent with those reported in previous studies (Čobanović et al, 2017;Lopez-Villalobos et al, 2018;Ariyarathne et al, 2019). However, Satoła et al (2017b) reported a lower value for MU in Polish Holstein-Friesian cows.…”
Section: Descriptive Statisticssupporting
confidence: 93%
“…The MU varies between individuals and is affected by many factors. Literature reported among others, the factors feed compositions (Correa-Luna et al, 2019), milking time (Bendelja et al, 2011), age at calving (Wood et al, 2003), stage of lactation and season of milking (Fatehi et al, 2012;Yin et al, 2012), herd and parity (Čobanović et al, 2017;Siatka et al, 2020), and genetics (Bendelja et al, 2011;Mucha and Strandberg, 2011;Rzewuska and Strabel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, deamination of amino acid and urea formation in the liver are reduced [7]. While some studies [10,16] reported that MU was lower in primiparous cows, other studies [9,14,15] found the highest MU concentration in primiparous cows and the lowest in multiparous cows.…”
Section: Discussionmentioning
confidence: 99%
“…Urea as a part of the non-protein fraction of nitrogen in milk represents the final product of protein metabolism in the rumen of ruminants [9]. In dairy cows, urea can be found as a component in blood, milk, saliva and urine.…”
Section: Introductionmentioning
confidence: 99%
“…Modern diets for highly productive cow are based on a high level of concentrated feed (up to 65% by nutritional value) that often causes disturbances in protein metabolism, which leads to lower indicators of productivity, reproduction, health, and premature culling of animals. It was found that the concentration of urea in blood and milk could be an indicator of these changes [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%